Impact of intraspecific variation on measurements of thermal tolerance in bumble bees. (July 2021) - Maebe, Kevin; De Baets, Annelien; Vandamme, Peter; Vereecken, Nicolas J.; Michez, Denis; Smagghe, Guy
Abstract: Climate change is an important driver of bee decline despite the fact that many species might respond to climate change differently. One method to predict how a species will respond to climate change is to identify its thermal tolerance limits. However, differences in thermal tolerance might also occur among distant populations of the same species based on their local environment or even among castes of social insects. Here, we investigated intraspecific differences in thermal tolerance among subspecies of the large earth bumble bee, Bombus terrestris (Apidae). We determined the critical thermal minima and maxima (CTmin and CTmax, respectively) of workers and queens from three lab-reared B. terrestris subspecies ( B. t. terrestris, B. t. audax, and B. t. canariensis ) which originated from different thermal environments. Our results showed that caste has an influence on critical thermal minima, with queens being most cold-tolerant, but the values of critical thermal maxima were not correlated to caste or size. The thermal tolerance of workers did not differ among the subspecies. Although heat tolerance was similar in queens, B. t. canariensis queens (originating from the warmest environments) were the least cold tolerant. Overall, we showed that B. terrestris may be generally robust against climate warming, but that particular subspecies and/or populations may be more vulnerable to extreme temperature variability. Future research should focus on responses of B. terrestris populations to short, extreme thermal events. Highlights: Intraspecies differences in thermal tolerance might occur between subspecies or even among castes of social insects. Critical thermal limits were measured for both workers and queens from three lab-reared B. terrestris subspecies. Thermal tolerances of workers did not differ among subspecies, but critical thermal minima (CTmin ) differed with caste. Heat tolerance was similar in queens, but B. t. canariensis queens (from warmest environments) were the least cold tolerant. Particular subspecies/populations of Bombus terrestris are likely to be more vulnerable to extreme temperature variability.